THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON REMOTE WORK ADAPTATION READINESS WITH THE MEDIATION ROLE OF INDIVIDUAL DIGITAL READINESS - Rita J D Atawarman; Siti Sholeha hasan; Rivaldo Lyonel Papilaya (PT. Jurnal Center Indonesia Publisher, 2026)
The development of digital technology and changes in the global work environment, particularly post-pandemic, have encouraged organizations to adopt remote and hybrid work systems. The successful implementation of these work systems is determined not only by technological readiness but also by organizational and individual factors. This study aims to analyze the influence of transformational leadership style and organizational culture on readiness to adapt to remote work, and to examine the mediating role of individual digital readiness in this relationship. This study uses a quantitative approach with an explanatory method. Data were collected through a Likert-scale-based questionnaire distributed online to employees working in remote or hybrid work systems using a purposive sampling technique. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) and PROCESS macro to test the direct relationship and mediation effects between variables. The results of this study are expected to provide theoretical contributions to the development of literature related to leadership, organizational culture, and individual digital readiness, as well as provide practical implications for organizations in designing leadership strategies, strengthening organizational culture, and developing digital competencies to improve readiness to adapt to remote work effectively and sustainably.